MAINTAIN A CULTURE OF INTEGRITY AT WORKPLACE DURING COVID-19 OUTBREAK - Fadillah Ismail; Nur Najwa Atirah Kamaludin (Jurnal Penyelidikan Sains Sosial, 2021)
Integrity is a powerful double-edged sword for companies today, is necessary forlong term success and corporate sustainability. Cultures of integrity are committed to doingthe right thing, not just as a matter of marketing or positioning, but as an uncompromisingstance embodied by the words and actions in any environment and situation encountered.Having integrity in the workplace has become very important these times, especially in thecurrent situation where all countries are facing with pandemic Covid19. Hence this paper asan initiative to the employer or organization in identifying factors that ensure the stability andpractice of a culture of integrity during Covid-19 by its employees in achieving the same goalsin any situation in the workplace or outside the organization.